Innovation in weight training for endurance events - Rohl, M.
Long distance athletes need workouts that develop resistance high levels of muscular fatigue that occurs from the repitive impact, stretching and contracting that they endure during competion. While most exercise phsiology tends to emphasize improvment in the area of aerobic performance and what way is the best way to improve econmy, threshold pace and VO2 max little work has been done on what is literally the pime movers of any sport - the periphial musclles. As any well conditioned 50k walker will tell you the real dibilation in the event and thus the the ulitmate limiting factor od perfromance is not dehydration or glycogen depletion but rather what most folks just call really tired muscles. The common approach to change this is to just go out and walk many miles. After all, those long walks build resitance to muscular fatigue as does completing high milage weeks. But it takes years for this adaptaion to occurr and once an athelte becomes acustomed to doing 3 and 4 hour waks the body's adapation response to that stress is diminished. I am in no way implying that one should forsake all the proper training techniques we engage in but the method I am going to describe should help any athlete at any level and in particular developing athletes and athletes who, for a variety of reasons, can not do the standard fare of 100+ miles weeks.